ANALISIS TINGKAT KEPUASAN GURU SMA SEBAGAI PENGGUNA APLIKASI ZOOM MEETING DI PERGURUAN ADVENT KOTA BEKASI DENGAN METODE PIECES FRAMEWORK DIMASA PANDEMI - Wellyne Victoria I; Jay Idoan Sihotang (Fakultas Tarbiyah dan Keguruan UIN Antasari, 2023)
Since the implementation of online learning, the Zoom Meeting application has experienced a significant increase in downloads by students and teachers to enable them to have face-to-face interactions and carry out teaching and learning activities as before the pandemic. This study was conducted to analyze the level of satisfaction of high school teachers who use the Zoom application at Advent Schools in Bekasi, which consists of two schools: Dharma Putra Advent School and Advent XIV Bekasi School. Data collection was carried out by distributing online questionnaires to 31 respondents. The researcher used the PIECES Framework method, which consists of six variables: performance, information, economic, control, efficiency, and service. Validity and reliability tests showed that the questionnaire results were valid and reliable. The results of this study showed that the overall average level of satisfaction of high school teachers at Advent Schools in Bekasi for each variable reached a satisfied category, where performance was 3.67 and 4.04, information was 3.51 and 4.02, economic was 3.62 and 4.02, control was 3.61 and 4.03, efficiency was 3.91 and 3.88, and service was 3.89 and 3.86.